Political Dynamics in Regional Legislative Election System to Strengthen Harmonization Political Participation - Harnawansyah, M. Fadhillah; Nazsir, Nasrullah; Suwaryo, Utang; Mariana, Dede (Universitas Malikussaleh, 2019)
Politics dynamics in regional legislative election system is found the problem there are conditions that are not in harmony between the format election system and the format regional government system. This problem can lead to low political representation of local communities by their legislators. This research contributes to gaining knowledge about the dynamics of regional politics and the ideal electoral system and harmony with local government systems that can be used in the future; with a high level of political representation, and to find out what factors are related to the regional legislative election system. This research uses ethnographic methods through in-depth interviews, direct participant observation, and documentation Data of 5 informants at the home of regional representatives, 5 political parties (in 2 different districts). His findings are that the electoral system still uses a semi-district model that is already out of proportion to the regional government system. Therefore this research is very important to change the improvement of the system which is also supported by a quality, integrity, professional, honest and fair election system; so that it will give birth to regional legislators who have a high level of political representation to their constituents; and at the same time can be effective in the administration of regional government.